Alcohol Consumption and Incident Stroke Among Older Adults. (10th February 2017) - Cunningham, Solveig A; Mosher, Aleena; Judd, Suzanne E; Matz, Lisa M; Kabagambe, Edmond K; Moy, Claudia S; Howard, Virginia J
Abstract: Objectives: This study examines the relationship between alcohol consumption and incident stroke among older adults and tests whether alcohol consumption contributes to observed race and sex differences in stroke. Method: Data are from a U.S. national cohort of black and white adults aged 45 and older, the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. Current and past drinking levels were reported at baseline (2003–2007). Participants who had never had a stroke were followed for adjudicated stroke events through September 2015 ( n = 27, 265). We calculated Cox proportional hazard models for stroke, adjusting for demographic, socioeconomic, behavioral, and health characteristics. Results: Participants, mean age 64.7 years, consumed on average 2.2 drinks/week and experienced 1, 140 first-time stroke events over median 9.1 years follow-up. Nondrinkers had a 12% higher risk of stroke than current drinkers; the risk of stroke among nondrinkers largely reflected high risks among past drinkers; these differences were explained by socioeconomic characteristics. Among current drinkers, light drinkers had significantly lower stroke risks than moderate drinkers after accounting for demographic, socioeconomic, behavioral, and health characteristics. Implications of alcohol did not differ between blacks and whites but did differ by sex: Especially among women, nondrinkers, and specifically past drinkers, had higher risks; these differences were largely explained by health characteristics and behaviors. Alcohol did not explain race and sex differences in stroke incidence. Discussion: Among older adults, those who used to, but no longer, drink had higher risks of stroke, especially among women; current light drinkers had the lowest risk of stroke.